2020
DOI: 10.1002/fuce.202000083
|View full text |Cite
|
Sign up to set email alerts
|

Another Chance for Classic AFCs? Experimental Investigation of a Cost‐Efficient Unitized Regenerative Alkaline Fuel Cell, Using Platinum‐Free Gas Diffusion Electrodes

Abstract: The big challenge of global phase-down of carbon dioxide emissions leads us to alternatives in storing electric energy from renewable sources. For the worldwide use of batteries and fuel cells very high amounts of precious electrode materials are needed. Batteries require rare earth metals and environmentally harmful Lithium, PEM fuel cells require noble platinum and iridium. Thus, an economical and eco-friendly alternative to lithium-ion-batteries should be found, especially for the use in domestic homes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…In 1959, Raney Ni was successfully used in a 5 kW AFC stack and delivered an operating efficiency of 60% in a 6 M KOH solution. , Later, the mid-1960s saw the application of AFCs as the power source for Apollo missions and space shuttle programs . Unfortunately, when operating with air in an automobile, KOH solution in AFCs will react with CO 2 to form carbonates whose precipitation can block the porous electrode and reduce the ionic conductivity of an electrolyte . Although AEMFCs can mitigate this issue, Ni with sluggish HOR reactivity cannot work efficiently in AEMFCs due to the very low OH – concentration (∼0.1 M). , To improve HOR performance, substantial efforts have been made toward catalyst discovery based on the Ni element over the past 68 years (Figure b), which have led to several effective improvement strategies such as alloying, ,,,, Ni nitridation, ,, alloy amorphization, and others (Figure c).…”
Section: Design and Assessment Of Nickel-based Hor Catalystsmentioning
confidence: 99%
“…In 1959, Raney Ni was successfully used in a 5 kW AFC stack and delivered an operating efficiency of 60% in a 6 M KOH solution. , Later, the mid-1960s saw the application of AFCs as the power source for Apollo missions and space shuttle programs . Unfortunately, when operating with air in an automobile, KOH solution in AFCs will react with CO 2 to form carbonates whose precipitation can block the porous electrode and reduce the ionic conductivity of an electrolyte . Although AEMFCs can mitigate this issue, Ni with sluggish HOR reactivity cannot work efficiently in AEMFCs due to the very low OH – concentration (∼0.1 M). , To improve HOR performance, substantial efforts have been made toward catalyst discovery based on the Ni element over the past 68 years (Figure b), which have led to several effective improvement strategies such as alloying, ,,,, Ni nitridation, ,, alloy amorphization, and others (Figure c).…”
Section: Design and Assessment Of Nickel-based Hor Catalystsmentioning
confidence: 99%
“…Thus, [53,54] devised a control strategy and proposed the incorporation of a fuzzy logic controller with the HE and fuel cell hybrid system to address power concerns caused by frequency changes. Although FLC has extensively been used for industrial applications, it does have certain limitations, it requires prior knowledge of the plant, for higher accuracy the fuzzy membership rules increase exponentially which results in lower speed and longer run time of the system [55], FLC is not capable of "learning" as it does not receive feedback, and the input variables have restricted usage [56]. Hence, there is a need for a more robust HE output control strategy that is capable of learning through feedback and captures the entire dynamics of the plant with ease without compromising the system speed and run time.…”
Section: Introductionmentioning
confidence: 99%
“…23 Nevertheless, it can perform with a good round-trip efficiency in bifunctional alkaline fuel cells, which is a property of rechargeable Li-ion batteries. 23 For application in URFCs, Ag has been combined with Ti and it was found that Ti−Ag/Ti (Ti−Ag film coated on Ti) showed good corrosion resistance that is comparable to bare Ti at high potentials and retained its current densities during long working mode at 2.0 V vs NHE under constant air purging. 24 Besides URFCs, Ag based catalysts have displayed different activities in AEMFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Ag is postulated as a possible alternative, since it is less expensive and shows a comparable ORR electrocatalytic activity to Pt in alkaline conditions. , Ag has been used in Siemens fuel cells in combination with nickel and titanium, and voltages around 800 and 900 mV at current densities of 400 and 200 mA cm –2 have been achieved, respectively . With gas diffusion electrodes (GDEs) made of Raney-silver and PTFE (polytetrafluoroethylene), voltages above 1 V and current densities around 30 mA cm –2 have been reached …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation